Identification of Probable Drug-Drug and Drug-Food Interactions in Hospitalized Patients With Chronic Renal Disease - Sari, Okta M.; Putra, Aditya M.P (Universitas Padjadjaran, Indonesia, 2024)
Chronic renal disease is a substantial health challenge in numerous countries worldwide, including Indonesia. Chronic renal disease patients frequently experience comorbidities and require multiple medications (polypharmacy). In patients receiving polypharmacy, it is necessary to monitor the occurrence of drug interactions. The current study analyzed the most probable of drug-drug interactions based on severity and management. Furthermore, to analyzed the most probable drug-food interactions based on severity and management in patients hospitalized with chronic renal disease. From September to October 2023, a cross-sectional study was carried out using retrospective data gathering. The population that attains the study criteria is referred to as the present research sample. The sampling methodology utilizes the saturated sample method. The tools utilized encompassed the Lexicomp® drug interaction checking application. The severity and management categories for probable drug-drug interactions and drug-food interactions are defined within the Lexicomp® application. The study analyzed medical data from 51 patients in total. The results of the current study showed that there were probable drug-drug interactions in 68.62% and drug-food interactions in 47.06% of patients hospitalized with chronic kidney disease. Based on severity, the most probable drug-drug interaction and drug-food interaction is in the moderate category. Based on the management, the most probable drug-drug interaction needs to be monitored, and the most probable drug-food interaction needs to be avoided concurrent administration with food. In patients with chronic renal disease, it is crucial to minimize and handle probable drug-drug and drug-food interactions.